The morphology and phonology of exponence - Trommer, Jochen (Oxford studies in theoretical linguistics ;, 2012)
Addressing the common problems, questions and solutions of exponence, this book contains contributions from leading specialists who formulate a coherent research programme which integrates the central insights of the last decades and provides challenges for the future.